Rheumatoid arthritis in African Colombians from Quibdo (2001)
Objectives: Little data is available on the prevalence and incidence of rheumatoid arthritis (RA) or the genetic and environmental factors that influence RA risk and severity in non-Caucasian populations. The prevalence of RA in Caucasians and some Native American populations is 1% or more; in contrast, low prevalences of RA have been reported in some African populations. We determined the hospital incidence (HI) and period prevalence (PP) of RA in African Colombians in Quibdo, Colombia, by using data collected at the Hospital San Francisco de Asis, a primary-to-tertiary care center. Genetic and immunologic studies of factors that influence RA risk and severity, such as HLA genes, immunoglobulin-A (IgA) rheumatoid factor (RF), and antikeratin antibodies (AKA) were performed. African Colombians with RA also were compared with Mestizo RA patients from Medellín, Colombia. Methods: To determine the HI, all the outpatient charts for 1995 were reviewed (n = 3,044). PP during 1996 (Jan-Dec) was assessed by stratified sampling of all African Colombians aged 18 or more having arthralgia. Participants completed a survey and a pretested standard questionnaire, had hands and feet X-rays, and provided a blood sample. Total and IgA RF were measured by turbidimetry and ELISA, respectively; AKA were assessed by indirect immunofluorescence on rat esophagus. HLA-DRB1 and DQB1 alleles were determined by polymerase chain reaction technique with primers of specific sequence and by reverse dot blot. Results: The HI was 0.65 cases per 1,000 person years. There were 321 individuals with arthralgia (0.3%; 95% CI, 0.28-0.3), 18 of whom fulfilled the American College of Rheumatology criteria for RA (PP in the general population, 0.01%; 95% CI, 0.008-0.02). Lower erosion scores were seen in African Colombian patients compared to Mestizos (n = 56), although duration of disease was similar in each group. No association between any HLA allele and RA risk or RA severity or between autoantibodies and RA severity was observed in African Colombians. Comparisons showed no significant differences between African Colombians and Mestizo patients in the presence of RF (total and IgA), AKA, age at onset, extra-articular manifestations, formal education level, and history of malaria. Conclusions: These results suggest that RA in African Colombian patients from Quibdo is rare, may be less severe in terms of radiographic damage than in Colombian Mestizo patients, and lacks association to HLA-DRB1 and DQB1 alleles. Additionally, RF (total and IgA) and AKA are not markers of progression and activity of the disease in this population.